Promotion Strategy Of Bri Branch Office Tangerang Merdeka In Increasing The Use Of The Brimo Application - Lucky Bahar Mattaliut, (Journal Research of Social Science, Economics, and Management, 2025)
Digital banking not only offers convenience, but also supports financial inclusion by reaching people who were previously underserved by conventional banking. This is a great opportunity for banks to improve their reach and quality of services. The purpose of this study is to determine the effectiveness of BRIMO's promotional strategy implemented at the BRI Tangerang Merdeka Branch Office. This study also aims to identify the factors that affect the mismatch between the growth of the number of accounts and the level of use of the BRIMO application. This research method uses a qualitative approach with case studies, the object of study in this study is the BRI work unit, while the research subjects include two main groups: internal and external, such as marketing officers, customer service (CS), and leaders of work units and external groups in this study are BRI customers who come from across generations, namely the Baby Boomers generation, Generation Y (Millennials), Generation Z and Generation Alpha. In this study, the sampling technique used is purposive sampling. The data analysis of this study uses the results of interviews and field notes. The results of the study show that the marketing strategy in the BRImo application can increase the number of customers at BRI Tangerang Merdeka through market segmentation, targeting, positioning, and implementation of the marketing mix which includes products, prices, distribution, and promotions. The obstacle to opening the BRIMO application in an effort to increase the number of customers at BRI Tangerang Merdeka comes from two factors.